Keep Liberia's forests - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The extent to which Liberia s forest resources have been destroyed by recent conflicts will be assessed by the National Environmental Commission (NECOLIB). With funds of almost t 1 million from the European Union, NECOLIB, with two USA- based...